Rigor Mortis — How Sloppy Science Creates Worthless Cures, Crushes Hope, and Wastes Billions by Richard Harris - Bauer, Henry (Journal of Scientific Exploration, 2018)
The sub-title of this book is accurately descriptive. The “science” underlying much of modern medical practice, particularly that associated with prescription drugs, is largely incompetent owing largely to faulty statistical approaches; and even when mistakes are pointed out, that does not ensure that practices change. The fundamental trouble is that the research enterprise has become far too big and far too competitive and is corrupted by commercial and political agendas and influences. One indication of the competition-induced hype and spin is the inflated self-lauding language in articles in medical journals; the frequency of such words as “novel”, “unprecedented” and the like increased by factors as great as 150 between 1974 and 2014 (pp. 190-1), The book mentions these fundamental issues but does not sufficiently emphasize them, indeed obscures them by suggesting remedies that do not get at the fundamental trouble: That researchers take more responsibility for good practices, for instance, is just whistling in the wind when the problem is systemic — as the book acknowledges in a few places: “The much harder challenge is changing the culture and the structure of biomedicine so that scientists don’t have to choose between doing it right and keeping their labs and careers afloat” (p. 4); “Biomedicine’s entire culture is in need of serious repair” (p. 167) — the prevalence of sloppiness, haste, corner-cutting, is amplified by the human penchant to “do what everyone is doing” (p. 187) because under present circumstances that seems effective in bringing visibility and prestige (p. 188).